Structural and Functional Comparison of the RING Domains of Two p53 E3 Ligases, Mdm2 and Pirh2 - Shloush, Jonathan (American Society for Biochemistry and Molecular Biology, 2011)
The tumor suppressor p53 maintains genome stability and prevents malignant transformation by promoting cell cycle arrest and apoptosis. Both Mdm2 and Pirh2 have been shown to ubiquitylate p53 through their RING domains, thereby targeting p53 for proteasomal degradation. Using structural and functional analyses, here we show that the Pirh2 RING domain differs from the Mdm2 RING domain in its oligomeric state, surface charge distribution, and zinc coordination scheme. Pirh2 also possesses weaker E3 ligase activity toward p53 and directs ubiquitin to different residues on p53. NMR and mutagenesis studies suggest that whereas Pirh2 and Mdm2 share a conserved E2 binding site, the seven C-terminal residues of the Mdm2 RING directly contribute to Mdm2 E3 ligase activity, a feature unique to Mdm2 and absent in the Pirh2 RING domain. This comprehensive analysis of the Pirh2 and Mdm2 RING domains provides structural and mechanistic insight into p53 regulation by its E3 ligases.